Strategi Advokasi Muhammadiyah Terhadap Jaya Musik Difabel Pasca Penataan Malioboro - Farid, Muhammad Rifa’at Adiakarti; Qoniah, Qoniah; Rahman, Nuril Endi (Jurnal Intervensi Sosial dan Pembangunan, 2025)
This study discusses the advocacy strategy of the Muhammadiyah Regional Leadership Social Service Council of Special Region of Yogyakarta regarding the problems facing Jaya Musik Malioboro. The background to the formation of this research is because DIY in 2024 has proclaimed itself as a Disability-Friendly Province.  Malioboro was also proposed as part of the Yogyakarta Philosophical Axis, because it was necessary to reorganize the Malioboro area. It turns out that efforts to organize street vendors in Malioboro have created problems for disabled musicians. This research uses a qualitative method descriptive. The results of the study show that the advocacy strategy of the Social Service Council using informal or implied communication methods to influence key decision-making elites to prioritize the principle of inclusivism is still ongoing.Keywords: Muhammadiyah, Malioboro, Advocacy Stategy, Disabilities